On the Discrete Nonlinear Hammerstein Systems With Non-symmetric Kernels - Dedagić, Fehim (Sarajevo Journal of Mathematics, 2024)
We study the nonlinear Hammerstein system $x(t)=\sum\limits_{s=1}^∞ {k(s,t)} f(s,x(s))+g(t)\quad (t\in\mathbb{N})$ with non-symmetric kernel $k(s,t)$. 2000 Mathematics Subject Classification. 47H30, 47H17